1998
DOI: 10.1097/00000542-199812000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Blood Volume Measurement at the Bedside Using ICG Pulse Spectrophometry 

Abstract: In most patients, the pulse method provides bedside measurement of BV without blood sampling (except for hemoglobin determination), with an estimated error less than 10%. In 10-30% of tests the method failed because of motion distortion of the record during the 10-min data collection period or because of insufficient pulse amplitude in the test tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 15 publications
5
84
0
2
Order By: Relevance
“…The ICG dye dilution curve can be used to measure hemodynamic parameters [13,14] . The currently available noninvasive method for measuring systemic hemodynamic parameters is pulse dye densitometry (PDD).…”
Section: Real-time Assessment Of Systemic Hemodynamic Statementioning
confidence: 99%
“…The ICG dye dilution curve can be used to measure hemodynamic parameters [13,14] . The currently available noninvasive method for measuring systemic hemodynamic parameters is pulse dye densitometry (PDD).…”
Section: Real-time Assessment Of Systemic Hemodynamic Statementioning
confidence: 99%
“…9,10 Propofol concentrations in whole blood were measured using high performance liquid chromatography as reported previously.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…This baseline level gradually decreases during the measurement as a result of the elimination of the remaining indocyanine green. Hence, the area under the indocyanine green concentration curve is underestimated but the resulting error is negligible, as previously reported [21]. The blood concentration of indocyanine green was determined with a pulse dye densitogram analyser (DDG-2001, A ⁄ K, Nihon-Kohden, Tokyo, Japan), which was connected to a clip device attached to the patient's left forefinger.…”
Section: Methodsmentioning
confidence: 59%
“…Haruna et al compared pulse dye densitometry using indocyanine green 10 mg with a 131 iodine-labelled human serum method for blood volume determination in healthy volunteers. They reported that in 30% of the cases, pulse dye densitometry measurement failed because of motion artifacts or low signal-to-noise ratio [21]. In the same study, pulse dye densitometry measurements failed in > 30% of patients after cardiac surgery because of motion distortion or insufficient pulse amplitude.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation